DISCERNING DYNAMICS OF RELIGIOSITY : A PHENOMENOLOGICAL ANALYSIS - Srivastava, Dr Pankaj (Innovative Research Thoughts, 2017)
Religiosity is not a homogeneous phenomenon. It functions multiple ways depending upon believer’s emotional relationship with the object of faith (Divinity, Holy Spirit, Personal God etc.) The present research intends first, to investigate the nature of religiosity considering the role of emotion in the making of believers’ subjectivity. The study categories different types of believers according to their aspirations for mundane and supra-mundane concerns. Second, it discerns the subjective and objective dimensions of believers’ consciousness by phenomenologically exploring the interface of emotion and perception in life- world of believers. And third, the study further attempts to apprehend the perception of believers by examining axiological and aesthetical dimensions of believer’s subjectivity.